Hyperthermic intrathoracic chemotherapy after extended pleurectomy and decortication for malignant pleura mesothelioma: an observational study on outcome and microcirculatory changes - Luzzi, Luca (J Thorac Dis, 2018)
BACKGROUND: In the treatment of malignant pleural mesothelioma the Hyperthermic Intra THOracic Chemotherapy (HITHOC) can improve the efficacy of pleurectomy and decortication with a local cytotoxic effect. However its biological impact in patient’s hemodynamic and microcirculatory changes were rarely investigated. Aim of this study is to describe our experience with HITHOC after pleurectomy and decortication evaluating the role of sublingual video-microscopy in assessing the microcirculatory changes in the perioperative period. METHODS: This is a prospective and observational study concerning 10 consecutive patients undergoing extended P/D followed by HITHOC. These patients underwent sublingual microcirculatory monitoring, which was adopted as a routine procedure since 2012. Haemodynamic parameters were collected at eight consecutive times: the day before surgery (T1), induction of anaesthesia (T2), surgical phase before HITHOC beginning (T3), 5 and 30 minutes after HITHOC start (T4 and T5, respectively), 5 minutes from HITHOC end (T6), after the admission in ICU (T7), at discharge from the ICU (T8). Cardiac output (CO) was calculated with MostCare. Systemic vascular resistance (SVR), oxygen delivery (DO(2)), and oxygen extraction rate (O(2)ER) were calculated using standard formulas. Arterial blood pressure and central venous pressure (CVP) were obtained with standard arterial and venous catheters. At the same times we assessed the sublingual microcirculation with Sidestream Dark Field technique. RESULTS: Hemodynamic and microcirculatory data were collected in 10 patients, 8 male and 2 females (mean age 68.6±9.0, and body surface area of 1.9±0.1 m(2)). All patients had arterial hypertension, and one patient had diabetes. The mean arterial pressure significantly decreased at T2, with respect to T1 (P=0.05). CO, CVP, DO(2), O(2)ER, and ScvO(2), did not change significantly over the time. All patients needed infusion of noradrenalin from T4 to T6. TVD significantly decreased from T1 to T3, T5, and T8. Similarly, PVD significantly decreased from T1 to T3 and T8, and MFI from T1 to T6 and T8. PPV and HI did not change over the study period. No correlation was found between hemodynamic parameters (MAP, CO, CVP, DO(2), O(2)ER, ScvO(2)) and microcirculatory data (TVD, PVD, PPV, MFI, HI), at any time of the study. CONCLUSIONS: In patients who receive HITHOC the fluid load can reduce the microvascular impairment restoring the normal tissue perfusion. This process takes days but is most evident in the first 72 h. The use of colloid and blood transfusion is much more effective in restoring microcirculation and reducing tissue damaging.